Kesenjangan Sosial dalam Novel Oliver Twist dan Nobody’s Boy: Kajian Intertekstual - Ahmad Abdullah Rosyid (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2021)
This research uses a novel from two different countries, namely England and France, entitled Oliver Twist by Charles Dickens and Nobody's Boy by Hector Malot. Even though they were written in different countries and periods, both novels seem to be related to one another. This research utilizes the theory of intertextuality as a reference for understanding the relationship between the two novels. The social conflict theory from Karl Marx is also used to support the analysis. The method used is descriptive qualitative data sources from the two selected novels. Data collection techniques are based on things related to social conflict relationships in the novel, data collected in the form of words, phrases, and sentences from dialogue and narration. Then, data validation is done by selecting the most dominant data for intertextual analysis. Data analysis is then done by comparing the two texts as the relationship of hypogram and transformation. The results obtained are a link between the two novels in the form of interrelation between the structure of the story, which includes the background, characters and characterizations, and social conflict in the form of social disparity between the bourgeois and proletarian classes. The text of Nobody's Boy is a transformation from Oliver Twist, which gives a description and emphasis on social inequalities that occur even in years that differ greatly between the two so that from these results, it can be concluded that the two novels have an intertextual relationship in terms of influence.